2012
DOI: 10.3390/cells1040667
|View full text |Cite
|
Sign up to set email alerts
|

The Myc Road to Hearing Restoration

Abstract: Current treatments for hearing loss, the most common neurosensory disorder, do not restore perfect hearing. Regeneration of lost organ of Corti hair cells through forced cell cycle re-entry of supporting cells or through manipulation of stem cells, both avenues towards a permanent cure, require a more complete understanding of normal inner ear development, specifically the balance of proliferation and differentiation required to form and to maintain hair cells. Direct successful alterations to the cell cycle r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…Sox2 and Neurog1 are in negative feedback, which allows proliferation and initiates differentiation. This differentiation interacts with retinoblastoma (Rb), Hes/Hey and IDs to regulate the cyclin-dependent kinases ( CDKs ), cross-react with e-proteins and define whether a cell cycle is progressing [ 98 , 100 , 105 , 106 ]. In the end, continuation depends on either knocking out Rb to continue proliferation or upregulating of Sox2 to jumpstart proliferation [ 107 , 108 ].…”
Section: Neurons Depend Upon Eya1 Sox2 Neurog1 And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sox2 and Neurog1 are in negative feedback, which allows proliferation and initiates differentiation. This differentiation interacts with retinoblastoma (Rb), Hes/Hey and IDs to regulate the cyclin-dependent kinases ( CDKs ), cross-react with e-proteins and define whether a cell cycle is progressing [ 98 , 100 , 105 , 106 ]. In the end, continuation depends on either knocking out Rb to continue proliferation or upregulating of Sox2 to jumpstart proliferation [ 107 , 108 ].…”
Section: Neurons Depend Upon Eya1 Sox2 Neurog1 And...mentioning
confidence: 99%
“…In addition to this cross-interaction, the spinal cord is further expanded by another bHLH set of genes, the Hes/Her genes [ 53 , 160 ] and the ID genes [ 9 , 99 , 161 ]. Starting with Sox2 expression, the neurosensory precursor cells are self-renewing and are driven by the Hes, ID and Myc genes to enhance proliferation [ 105 ]. The expansion changes by an oscillation to interact with Hes/Ascl1 , for example.…”
Section: The Brainstem Is Transformed From the Spinal Cordmentioning
confidence: 99%
“…In particular, the absence of mammalian inner ear sensory hair cell (HC) regenerative capabilities drove researchers towards gathering clues on their differentiation and maintenance; this would help in the future design of approaches for enhancing HCs' maintenance power and eventually inducing their regeneration. 1 Mechanisms responsible for cell cycle exit, epithelium patterning and post-mitotic cell cycle arrest of maturing and mature HCs have been a challenging field of focus in auditory research, and the information so far gathered is rather scarce. 2 For example, in a mouse line lacking cyclin-dependent kinase inhibitor p19 Ink4d (p19), Chen et al 3 have shown that p19 does not influence mouse embryonic stereotyped patterning of cochlea zone of non-proliferating cells into the organ of Corti that is composed of a mosaic of sensory HCs and supporting cells occurring around embryonic days 15.5 and 17.5.…”
mentioning
confidence: 99%